Assessment of Regional Ventilation During Recruitment Maneuver by Electrical Impedance Tomography in Dogs - Ambrósio, Aline Magalhães; Sanchez, Ana Flávia; Pereira, Marco Aurélio Amador; Andrade, Felipe Silveira Rego Monteiro De; Rodrigues, Renata Ramos; Vitorasso, Renato de Lima; Moriya, Henrique Takachi; Fantoni, Denise Tabacchi (Frontiers in Veterinary Science, 2022)
Background During protective mechanical ventilation, electrical impedance tomography (EIT) is used to monitor alveolar recruitment maneuvers as well as the distribution of regional ventilation. This technique can infer atelectasis and lung overdistention during mechanical ventilation in anesthetized patients or in the ICU. Changes in lung tissue stretching are evaluated by monitoring the electrical impedance of lung tissue with each respiratory cycle. Objective This study aimed to evaluate the distribution of regional ventilation during recruitment maneuvers based on the variables obtained in pulmonary electrical impedance tomography during protective mechanical ventilation, focusing on better lung recruitment associated with less or no overdistention. Methods Prospective clinical study using seven adult client–owned healthy dogs, weighing 25 ± 6 kg, undergoing elective ovariohysterectomy or orchiectomy. The animals were anesthetized and ventilated in volume-controlled mode (7 ml.kg−1) with stepwise PEEP increases from 0 to 20 cmH2O in steps of 5 cmH2O every 5 min and then a stepwise decrease. EIT, respiratory mechanics, oxygenation, and hemodynamic variables were recorded for each PEEP step. Results The results show that the regional compliance of the dependent lung significantly increased in the PEEP 10 cmH2O decrease step when compared with baseline (p < 0.027), and for the nondependent lung, there was a decrease in compliance at PEEP 20 cmH2O (p = 0.039) compared with baseline. A higher level of PEEP was associated with a significant increase in silent space of the nondependent regions from the PEEP 10 cmH2O increase step (p = 0.048) until the PEEP 15 cmH2O (0.019) decrease step with the highest values at PEEP 20 cmH20 (p = 0.016), returning to baseline values thereafter. Silent space of the dependent regions did not show any significant changes. Drive pressure decreased significantly in the PEEP 10 and 5 cmH2O decrease steps (p = 0.032) accompanied by increased respiratory static compliance in the same PEEP step (p = 0.035 and 0.018, respectively). Conclusions The regional ventilation distribution assessed by EIT showed that the best PEEP value for recruitment maintenance, capable of decreasing areas of pulmonary atelectasis in dependent regions promoting less overinflation in nondependent areas, was from 10 to 5 cmH2O decreased steps.